The Impact of the Baznas Z-Auto Program on Improving the Community's Economy in Kab. Barru (Sharia Economic Analysis) - HS, Lifityani; Muhammadun, Muzdalifah; Damirah, Damirah; Idris, Masyar; Bahri, Andi (Jurnal Ilmu Manajemen Profitability, 2025)
Zakat-based empowerment programs are an important instrument in supporting sustainable community development, yet studies assessing their effectiveness at the local level remain limited. In particular, empirical evidence on how zakat programs align with sharia economic principles while enhancing the welfare of beneficiaries is still underexplored. This study seeks to fill this gap by examining the impact of the BAZNAS Z-Auto Program on community economic empowerment in Barru Regency. The research employed a mixed-method case study approach that combined descriptive quantitative and qualitative analysis, allowing for an in-depth understanding of both program outcomes and implementation mechanisms. Data were collected from mustahik beneficiaries, program documentation, and institutional reports to capture the program’s effectiveness and challenges. The findings indicate that the Z-Auto Program has positively contributed to improving the economic welfare of mustahik through the provision of productive facilities and targeted assistance. Moreover, the integration of sharia principles is evident: siddiq (truthfulness) through transparent beneficiary selection and reporting, amanah (trustworthiness) in fund management, fathonah (professionalism) in planning and mentoring, and tabligh (transparency) in communication. While some challenges remain in disseminating information broadly, the overall synergy of these principles enhances program sustainability. These results enrich the literature on zakat-based empowerment and provide practical insights for policymakers and zakat institutions in designing more effective and sharia-compliant community development strategies.